Microfinance in Bangladesh : A comparative study between interest-free and conventional microfinance - Al Mamun, Abdallah (My University, 2023)
In Bangladesh, initiatives to reduce poverty through microfinance that follows conventional models and interest-free frameworks are relatively new. This study is carried out to evaluate the operational differences and facilities provided by traditional and interest-free microfinance institutions (IFMIFs). Secondly, this study explored the services impact of conventional and IFMIFs on the poverty reduction of Bangladesh using data from 2010 to 2020 and the ordinary least squared estimation approach. This research studies four poverty indicators: upper poverty rate, extreme poverty rate, infant mortality rate, and basic sanitation rate for estimating the impact of microcredit disbursement. The result found that interest-free microcredit disbursement can help to reduce both the upper poverty and infant mortality rates, but the opposite result is found in eliminating extreme poverty. Traditional microfinance institutions’ loan disbursement has a positive impact on the upper poverty level. Furthermore, IFMFIs have a positive impact on increasing the basic sanitation rate, but conventional MFIs have negative effects on basic sanitation. In contrast, IFMFIs credit disbursement has a better impact on poverty alleviation compared to traditional microfinance institutions in Bangladesh. Finally, this study firmly believes that this research will bring a revolutionary sight among academicians, policymakers, government and other stakeholders for alleviating poverty through IFMIs credit disbursement in Bangladesh.

Bangladeş'te, geleneksel modelleri ve faizsiz çerçeveleri izleyen mikrofinans yoluyla yoksulluğu azaltmaya yönelik girişimler nispeten yenidir. Bu çalışma, geleneksel ve faizsiz mikrofinans kurumlarının (IFMIF'ler) sağladığı operasyonel farklılıkları ve kolaylıkları değerlendirmek amacıyla yapılmıştır. İkinci olarak, bu çalışma, 2010'dan 2020'ye kadar olan verileri ve sıradan en küçük kareler tahmin yaklaşımını kullanarak geleneksel ve IFMIF'lerin Bangladeş'teki yoksulluğun azaltılması üzerindeki etkisini araştırdı. Bu araştırma dört yoksulluk göstergesini dikkate almaktadır: mikro kredi kullanımının etkisini tahmin etmek için üst yoksulluk oranı, aşırı yoksulluk oranı, bebek ölüm oranı ve temel sanitasyon oranı. Sonuç, faizsiz mikro kredi ödemesinin hem üst yoksulluğu hem de bebek ölüm oranlarını azaltmaya yardımcı olabileceğini, ancak aşırı yoksulluğun ortadan kaldırılmasında bunun tersi bir sonucun bulunduğunu ortaya koydu. Geleneksel mikrofinans kurumlarının kredi kullandırımı, üst yoksulluk düzeyi üzerinde olumlu bir etkiye sahiptir. Ek olarak, IFMFI'lerin temel sanitasyon oranını artırmada olumlu bir etkisi vardır, ancak geleneksel MFI'lerin temel sanitasyon üzerinde olumsuz etkileri vardır. Buna karşılık, IFMFI'nin kredi ödemesi, Bangladeş'teki geleneksel mikrofinans kurumlarına kıyasla yoksulluğun azaltılması üzerinde daha iyi bir etkiye sahiptir. Son olarak, bu çalışma, bu araştırmanın akademisyenler, politika yapıcılar, hükümet ve diğer paydaşlar arasında Bangladeş'te IFMI'nin kredi ödemesi yoluyla yoksulluğu azaltmak için devrim niteliğinde bir görüş getireceğine inanıyor.
Bangladeş'te mi̇krofi̇nans : Fai̇zsi̇z ve geleneksel mi̇krofi̇nans arasında karşılaştırmalı bi̇r çalışma
Keywords: Bangladesh; Bangladeş; Bankalar ve bankacılık; Banks and banking; conventional microfinance; Dini yönleri; faiz; Finance; Finans; Islam; Islamic microfinance; interest; İslam; İslami mikrofinans; konvansiyonel mikrofinans; povert; Religious aspects; yoksulluk